Examining the Role of Theory in Qualitative Research: A Literature Review of Studies on Chinese International Students in Higher Education - Heng, Tang Tang (Journal of International Students, 2020)
Scholars argue that higher education and international student research suffer from a lack of theoretical engagement, which is epistemologically limiting. This is troubling as theory frames research design and findings and pluralizes our understanding of a phenomenon. Given the large number of Chinese international students worldwide (and related research), this article uses them as an analytic example to understand the role of theories in shaping qualitative research designs, focuses, and findings. I reviewed 43 qualitative research articles on Chinese international students’ experiences. Twenty-eight percent of the articles were found to lack theoretical engagement. When used, theories clustered around acculturation and sociocultural perspectives. Sixty percent of the articles foregrounded student challenges, as opposed to student agency or changes (40%). I discuss the consequences of a lack of theoretical engagement or diversity on how we understand and support international students.